Speech intelligibility of the diastratic varieties of Philippine English - Tak, Jin-young; Zipagan, Maribel; Kwak, Eun Joo (Universitas Syiah Kuala, 2023)
The rise of English globalization has prompted speech production variations that reveal the cultural and social backgrounds of the different speakers. However, intelligibility issues of the different varieties have also become a concern. Thus, the present study attempted to assess the intelligibility of Philippine English (PE) diastratic varieties speech recordings produced by local Cebuano speakers. Further, it aimed to specifically evaluate the speakers production differences, rate the intelligibility of the language varieties, and determine the effect of language variety on the listener-evaluators in terms of intelligibility and distraction ratings. Using an exploratory sequential mixed method design, the speech participants in this study were carefully chosen through multistage sampling first by social class and then by phonological variations. The three final sample speakers out of the initial eighteen were finally categorized as acrolect, mesolect, and basilect. The evaluating groups included English language users from the USA, the Philippines, Korea, and Thailand, and each group represented a region in Kachrus concentric circle of the World Englishes model. The results identified acrolect as the most intelligible variety followed by mesolect. Basilect, on the other hand, was considered very distracting to the evaluator groups, resulting in a significantly low intelligibility score. Thai evaluators gave the lowest intelligibility ratings, which may be attributed to two factors, L1 interference and unfamiliarity of L2 variation. Finally, future directions and implications in the classroom and industry are stated to create a sense of cultural awareness and to promote a deeper intercultural understanding that comes with international intelligibility.